The Right to Privacy: Tinjauan terhadap Penyalahgunaan Data Pribadi dalam Perspektif HAM - Saputra, Wahyudi (Res Judicata, 2023)
The privacy movement was created by Warren and Brandhuis, who wrote an article in Harvard Law School Journal title "The Right to Privacy" is the right to a person's privacy not to be invaded by others or the government. Laws must recognize and protect an individual's right to privacy. Personal data protection at the global level is regulated by several regulations such as the UDHR and ICCPR.The writing method used in this paper is a normative juridical research method which uses literature references as research data in this paper. The results of this research, namely in ratifying the UDHR and ICCPR regardingThe Right to Privacy As part of the protection of human rights, the Indonesian government is seen as not yet serious about implementing it thoroughly. The PDP Bill, which should be the main focus of the government, is to protect the privacy and security of citizens' data, which has not yet become a top priority. The use of personal data in registration of various applications and regulations for private interests, especially NIK, is not in accordance with the required purposes and creates a potential risk of misuse by cybercriminals and corporations who use the personal data collected. Problems in law enforcement in Indonesia related to privacy violations still occur frequently because there is no national data protection authority that is specifically responsible for data privacy.Keywords: The Right to Privacy, Human Rights, Personal Data